2017
DOI: 10.1159/000484240
|View full text |Cite
|
Sign up to set email alerts
|

Attention Deficit Hyperactivity Disorder Symptoms are Common in Patients in Opioid Maintenance Treatment

Abstract: Introduction and Aims: Knowledge of attention deficit hyperactivity disorder (ADHD) symptoms among patients in opioid maintenance treatment (OMT) is important for treatment optimization and yet limited. We investigated the prevalence of ADHD symptoms, and factors associated with high ADHD symptom burden in a group of Norwegian OMT patients. Methods: We interviewed individuals entering OMT across Norway in 2 steps between 2012 and 2016. ADHD symptoms were measured by the Adult ADHD Self-Report Scale (ASRS; n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 41 publications
2
11
4
Order By: Relevance
“…Of note were the high prevalence of major depressive disorder (31%), ADHD (27%), and generalized anxiety disorder (23%) compared with general population estimates of 7%, 11%, and 3%, respectively 14 . Similarly high rates of these diagnoses in the opioid use disorder population have been reported by others 15‐18 . Most patients in this study reported that their comorbid psychiatric disorders played a significant role in their opioid dependence, as their psychiatric symptoms were greatly ameliorated by opioids.…”
Section: Discussionsupporting
confidence: 84%
“…Of note were the high prevalence of major depressive disorder (31%), ADHD (27%), and generalized anxiety disorder (23%) compared with general population estimates of 7%, 11%, and 3%, respectively 14 . Similarly high rates of these diagnoses in the opioid use disorder population have been reported by others 15‐18 . Most patients in this study reported that their comorbid psychiatric disorders played a significant role in their opioid dependence, as their psychiatric symptoms were greatly ameliorated by opioids.…”
Section: Discussionsupporting
confidence: 84%
“…The prevalence estimates may differ according to the type of substance used and the subpopulations or treatment modality. For example, the following populations of patients in opioid maintenance treatment (OMT) were screened positively for ADHD: in Norway, 33% of OMT patients [5], in Austria, in 50% of children and 17% of adults of the mainly male prison inmates in OMT [6], and in Italy, 11.2% of OMT patients [7]. In the methamphetamine-using population of one hospital’s psychiatric center, the prevalence of the ADHD diagnosis went up to 55.6% [8].…”
Section: Introductionmentioning
confidence: 99%
“…It was recommended by Kessler et al [ 19 ] as an initial screening tool for ADHD and has been used, to some extent, in populations with SUDs [ 19 , 20 , 21 ]. The scoring method is similar to that of the full version, with the summed score ranging from 0–6, and a score ≥ 4 is considered to be a likely positive screen for ADHD [ 3 , 4 , 22 ]. Compared to the 18-item version, which was validated in a representative community sample, Daigree et al [ 20 ] reported a much higher sensitivity (87.5%) and much lower specificity (68.6%) for the 6-item scale in a population with SUDs [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…A high prevalence of psychiatric comorbidity, mental distress, and attention deficit hyperactivity disorder (ADHD) has been observed in a number of patient populations with substance use disorder (SUD) [ 1 , 2 ]. However, knowledge of the impact of ADHD symptomatology as a co-occurring condition among opioid-dependent patients enrolled in opioid maintenance treatment (OMT) is sparse [ 3 , 4 ]. The core symptoms of ADHD are impulsivity, hyperactivity, and inattention (IHI) and difficulties performing executive functions.…”
Section: Introductionmentioning
confidence: 99%